Liquid Soap with Active Ingredients of Methanol Extract of Sambang Darah Leaves (Excoecaria cochinchinensis L.): Formulation, Characterization, and Antibacterial Activity - Fatkhurrachman Fatkhurrachman; Avidlyandi Avidlyandi; Devi Nurhasana; Dina Erliana; Munifilia Eka Sari; Charles Banon; Risky Hadi Wibowo; Morina Adfa (Department of Chemistry - Universitas Bangka Belitung, 2023)
The methanol extract of sambang darah leaves (Excoecaria cochinchinensis L.) contains flavonoids, saponins, tannins and triterpenoids which have the potential as antibacterial compounds. The goal of this research is to produce liquid soap that preparations with four formulas by varying the methanol extract of sambang darah leaves as the active ingredient, characterizing, and understanding its antibacterial activity. Organoleptic tests, foam stability, pH, specific gravity, and viscosity were all used to characterize liquid soap. The best results were obtained with liquid soap formulation 3 (3 g extract), which had foam stability of 84.10%, a pH of 9.62, specific gravity of 1.03 g/mL, and viscosity of 492.933 cP. The organoleptic test revealed that the liquid soap was a homogeneous viscous liquid with a blackish-brown color and a characteristic extract odor. The inhibition zone for antibacterial activity against Staphylococcus aureus and Escherichia coli was 9.15 mm and 13.72 mm, respectively. In antiseptic tests, all soap formulas reduced bacteria on the thumb.